Lough Sheeauns, Connemara, Co. Galway (profile SHE IV): exploratory investigations of peat deposit from near the lake margin - Michael O extquotesingleConnell; Karen Molloy (PANGAEA, 2018)
Results of exploratory pollen analytical investigations and LOI of a peat deposit from the L. Sheeauns basin are reported. The investigations complement the detailed investigations (profile SHE III) from the lake itself. There are no 14C dates. Features that enable an approximate chronology to be attached include the rise of Alnus (Boreal/Atlantic transition) and the final decline of Pinus (c. 3000 BP). The profile was published in Molloy and O extquotesingleConnell 1991.